It is not death to die a new biography of Hudson Taylor - Cromarty, Jim; China Inland Mission; Overseas Missionary Fellowship International (Ross-shire, UK Christian Focus, 2001)
Includes bibliographcial references and index.
Keywords: Taylor, James Hudson, -- 1832-1905 -- biography; Missions -- China -- biography